2022
DOI: 10.1088/1361-6463/ac6c5f
|View full text |Cite
|
Sign up to set email alerts
|

Improved barrier homogeneity in Pt/Al0.75Ga0.25N Schottky barrier diodes by graphene interlayer

Abstract: Pt/Al0.75GaN Schottky barrier diodes (SBDs) with graphene (w/ Gr) and without graphene (w/o Gr) interlayer between metal and semiconductor were fabricated to determine the effects of Gr interlayer on the device electrical characteristics. The temperature dependent current–voltage (I–V) and capacitance–voltage (C–V) characteristics were systematically measured and comparably analyzed for both structures. The ideal factor (n) and Schottky barrier height (SBH) were determined by the thermionic emission model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…They are essentially suitable for various applications targeting low losses and high operating frequencies and temperatures. This special issue evaluates a series of GaN-and AlGaN-based electronic devices proposed by Chinese researchers, such as Schottky barrier diodes (SBDs) [19], metal-oxide-semiconductor field effect transistors (MOSFETs) [20], high electron mobility transistors (HEMTs) [21][22][23][24][25], and so forth.…”
Section: Electronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are essentially suitable for various applications targeting low losses and high operating frequencies and temperatures. This special issue evaluates a series of GaN-and AlGaN-based electronic devices proposed by Chinese researchers, such as Schottky barrier diodes (SBDs) [19], metal-oxide-semiconductor field effect transistors (MOSFETs) [20], high electron mobility transistors (HEMTs) [21][22][23][24][25], and so forth.…”
Section: Electronic Devicesmentioning
confidence: 99%
“…Ran et al [19] studied the electrical properties of SBDs with and without graphene interlayer between metal and semiconductor. The inclusion of graphene increased the Schottky barrier height from 1.194 eV to 1.443 eV, as determined by the thermionic emission model and barrier inhomogeneity model.…”
Section: Electronic Devicesmentioning
confidence: 99%
“…Similar findings were declared in literature reports. For instance; Ran et al [33] prepared Pt/Al 0.75 Ga 0.25 N Schottky diode (SD) with and without graphene interlayer between metal and semiconductor to determine the effect of the graphene interlayer on the device electrical properties. The results revealed that the performance of the AlGaN SD prepared with graphene improved.…”
Section: Diode Characteristicsmentioning
confidence: 99%